Sumbangan seorang tokoh pemuziuman : Prof. Dato' Dr.Othman Yatim - Mohd Azman, bin Md Zakaria (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study is a contribution to the study of a character to the museum. This study was conducted to investigate the contribution in terms of research and studies that have been carried out by a manifest character of our country, and examine the impact assessments that have been made by him to the preservation of our heritage and culture, as well as documenting his contributions to the country's arts and heritage. This can be translated through an interview conducted on Prof. Dato’ Dr. Othman Bin Mohd Yatim orphans themselves are the leaders researchers and options supported by the facts gathered from interviews with other informants as well as writing his book and also support the fact that depictions of newspaper articles about the research he has done. Results of the study found that the studies that have been conducted by prominent researcher’s choices lead to his expertise in the field of preservation of heritage and culture which can be seen from the results of his findings on the gravestones, cannons and also the graves of Orang Kaya Ngah Ibrahim. Other than that, to show the impact studies that have been done by the leaders of this manifest to the general public, there are hundreds of books and scientific literature that has been published to keep the history of art and cultural heritage in order to remain and not be forgotten by the locals. In addition, hundreds of seminars which were attended by him also have an effect on the development and improvement of the current museum. The results of this study also have implications for the museum because the study shows results that have been done by a figure manifest. These studies also have implications for future research because this research is the first writing on Prof. Dato' Dr. Othman orphans. In addition, this study also represents recognition on the contribution made by him as a figure manifest.